“SMART HELMET – FALL DETECTION OF RIDERS USING INERTIAL SENSORS AND TO AVOID ACCIDENTS OCCURRENCE” (International Journal of Food and Nutritional Sciences, 2022)
Motorcycle accidents are occurring with intimidating frequency and the number of losses of lives is also adding up day by day. The smart helmet is a wearable device designed to enhance the safety and security of motorcycle riders. It uses IR detectors, GPS, GSM modules, alcohol detectors and ultrasonic detectors. It provides an array of features. The smart helmet has a module that tries to determine whether the rider is wearing the helmet or not. The vehicle is not able to start, if the rider did not wear the helmet and if he is an alcoholic. For this we use IR detectors and alcohol detectors. The ultrasonic detector provides accident avoidance by detecting any objects approaching the rider from the rear, which alerts the rider by a beep sound and displays the information on the LCD screen. GPS and GSM modules are used in accident detection. Overall, the smart helmet provides an advanced position of safety and security to motorcycle riders, making their trip safer and further secure